Floristic composition, community structure, diversity and biomass of trees species in three forest reserves at Pulau Pangkor, Perak, Malaysia - Z., Ahmad Fitri; I., Faridah Hanum; Saari, Nurul Shida; M., Morazlinda; N. A., Nik Norafida; Latiff, A.; Ludin, Rosni; Kamaruddin, Kamarulizwan; N. H., Nik Hazlan (Forestry Department Peninsular Malaysia, 2019)
.A study to determine species composition, community structure, and biomass of trees was carried out in three forest reserves at Pulau Pangkor, Perak. Sixteen plots of 20 m x 20 m were established at Pangkor Utara Forest Reserve (4 plots), Sungai Pinang Forest Reserve (4 plots) and Pangkor Selatan Forest Reserve (8 plots) which covered a total area of 0.64 ha. All trees with diameter at breast height of 5 cm and above were measured, tagged, identified and recorded. As a result, a total of 637 trees was measured from 118 species, 78 genera and 42 families. Plots in Sungai Pinang FR, recorded 169 individuals representing 57 species from 48 genera and 27 families. Meanwhile, in Pangkor Utara FR, a total of 148 individuals represents 46 species from 35 genera and 24 families. In Pangkor Selatan FR, a total of 320 individuals represents 76 species from 47 genera and 31 families. The value of Shannon Diversity Index in Sungai Pinang, Pangkor Utara and Pangkor Selatan were 3.37, 3.31 and 3.84, respectively. In terms of density, the highest density was recorded in the plot at Sungai Pinang FR with 1056 ind/ha. The highest amount of basal area (BA) was also recorded in Sungai Pinang FR, 62.18 m ² /ha. Leguminosae was the most important family recorded in Sungai Pinang FR with Important Index (FIVi) of 16.67%, while Dipterocarpaceae was the most important family in both Pangkor Utara and Pangkor Selatan FRs with Important Value Index (IVi) of 15.68 and 31.98%, respectively. Fifteen endemic species were reported in the three forest reserves including two species which have restricted distribution in Perak state (Fordia unifoliata and Shorea lumutensis). Plots in Sungai Pinang FR lead the total estimated tree biomass with 987.48 t/ha was followed by plots in Pangkor Selatan FR with an estimated tree biomass of 921.89 t/ha and 729.96 t/ha in Pangkor Utara FR, respectively. Dipterocarpaceae dominated the estimate biomass value in all three forest reserves with 295.38t/ha in Sungai Pinang FR, 185.90 t/ha in Pangkor Utara FR and 549.94 t/ha in Pangkor Selatan FR.